Unilateral optogenetic kindling of hippocampus leads to more severe impairments of the inhibitory signaling in the contralateral hippocampus - Tescarollo, Fabio Cesar; Valdivia, Daniel; Chen, Spencer; Sun, Hai (Frontiers in Molecular Neuroscience, 2023)
The kindling model has been used extensively by researchers to study the neurobiology of temporal lobe epilepsy (TLE) due to its capacity to induce intensification of seizures by the progressive recruitment of additional neuronal clusters into epileptogenic networks. We applied repetitive focal optogenetic activation of putative excitatory neurons in the dorsal CA1 area of the hippocampus of mice to investigate the role of inhibitory signaling during this process. This experimental protocol resulted in a kindling phenotype that was maintained for two weeks after the animals were fully kindled. As a result of the different phases of optogenetic kindling (OpK), key inhibitory signaling elements, such as KCC2 and NKCC1, exhibited distinct temporal and spatial dynamics of regulation. These alterations in protein expression were related to the distinct pattern of ictal activity propagation through the different hippocampal sublayers. Our results suggest the KCC2 disruption in the contralateral hippocampus of fully kindled animals progressively facilitated the creation of pathological pathways for seizure propagation through the hippocampal network.Upon completion of kindling, we observed animals that were restimulated after a rest period of 14-day showed, besides a persistent KCC2 downregulation, an NKCC1 upregulation in the bilateral dentate gyrus and hippocampus-wide loss of parvalbumin-positive interneurons. These alterations observed in the chronic phase of OpK suggest that the hippocampus of rekindled animals continued to undergo self-modifications during the rest period. The changes resulting from this period suggest the possibility of the development of a mirror focus on the hippocampus contralateral to the site of optical stimulations. Our results offer perspectives for preventing the recruitment and conversion of healthy neuronal networks into epileptogenic ones among patients with epilepsy.